Schwannoma with rhabdomyoblastic differentiation - A unique variant of malignant triton tumor - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2003)
A 54-year-old woman presented with intractable perianal, bilateral buttock, and radiating thigh/calf pain. An MRI scan showed an intradural, contrast-enhancing, ovoid mass in the cauda equina region at L1-L2. At laminectomy, the ovoid mass arose from a nerve root and, intact, was gross totally resected. Histologically, the dominant pattern was that of schwannoma. One year thereafter, the symptoms recurred. An MRI scan demonstrated an irregular, heterogeneously enhancing tumor recurrence. A repeat laminectomy disclosed a large fleshy tumor involving multiple nerve roots. The lesion was subtotally resected and showed pluridirectional differentiation toward embryonal rhabdomyosarcoma, primitive neuroectodermal tumor, and rare malignant epithelial cells. Review of the original tumor disclosed only foci of embryonal rhabdomyosarcoma and primitive neuroectodermal tumor. Based upon available data regarding divergent differentiation in peripheral nerve sheath tumors, this is a unique, previously undescribed tumor demonstrating rhabdomyosarcomatous, primitive neuroectodermal tumor and scant epithelial differentiation in a schwannoma. In essence, it is a variant of malignant Triton tumor because of its origin in a tumor consisting of well-differentiated Schwann cells. It supports the contention that the Schwann cell is the source of a variety of heterologous elements in nerve sheath tumors.
Keywords: malignant peripheral nerve sheath tumor; primitive neuroectodermal tumor; schwannoma; NERVE SHEATH TUMORS; BENIGN GLANDULAR SCHWANNOMA; NEURILEMOMA; ORIGIN